ANALYSIS OF EMPLOYEE WORKLOADS USING THE WORKLOAD ANALYSIS (WLA) METHOD ON MULTI-LINE NON-FOLDING PACKAGING WORKSTATION PT MARIMAS PUTERA KENCANA - Maharani, Maria Goretti Beata Setyo; Susanto, Novie (Program Studi Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2024)
AbstractPT Marimas Putera Kencana is a company specializing in the production of food and beverages, withits primary product being powdered drinks. The company operates a multi-line non-folding packagingwork station, which is deemed less efficient compared to a multi-line folding machine. This workstationfaces challenges related to labor efficiency, particularly during break hours, as the machine continuesto operate without pausing production. Consequently, an assessment of the operators' workload wasconducted to determine the optimal number of operators required. This study focuses on the workloadmeasurement of the morning shift at the multi-line non-folding packaging work station, operating foran effective duration of 7 hours. The Workload Analysis (WLA) method was employed for this purpose.The data processing in this research included tests for data uniformity and adequacy, total productionoutput, working hours, performance ratings, and operator allowances. The results of the calculationsrevealed that the operators' workload was 149,964%, indicating a significant excess over the maximumacceptable limit of 100%. Based on this workload value, it was determined that the optimal number ofoperators required is two.Keywords: employee optimization, workload, Workload Analysis (WLA)